Critical appraisal and hazards of surface electromyography data acquisition in sport and exercise - Clarys, J. P.; Scafoglieri, A.; Tresignie, J.; Reilly, T.; Van Roy, P. (Asian Journal of Sports Medicine, 2010)
The aim of this critical appraisal and hazards of surface electromyography (SEMG) is to enhance the data acquisition quality in voluntary but complex movements, sport and exercise in particular. The methodological and technical registration strategies deal with telemetry and online data acquisition, the placement of the detection electrodes and the choice of the most adequate normalisation mode.